Advantages and disadvantages of use of digital collections in the process of education - Vrana, Radovan (Array, 1999)
Paper shows one possible way of using information technology and the Internet in the process of education at the Faculty of Philosophy in Zagreb. With projects like the one described, Digital collection of exam materials, students accept new technologies introduced to them on everyday basis and also learn how to use the online content for their study.